PENGGUNAAN VAKSIN DEBRIS SEL Aeromonas hydrophila DENGAN INTERVAL WAKTU BOOSTER BERBEDA TERHADAP RESPONS IMUN LELE DUMBO (Clarias gariepinus Burchell) - Mulia, Dini Siswani (Universitas Muhammadiyah Purwokerto, 2007)
The aims of this research was to determine effect vaccination of cell debris of A. hydrophila by 1-3 times booster with 2nd week time interval on African catfish immune response. The research was constructed as CRD with five treatments and three replicates, i.e. K : control; D1 : without booster; D2 : once booster; D3: twice booster, and D4 : three times booster. African catfish of 10-13 cm length and 12-16 g of weight were used, with the number of 15 fish for each treatment. Intramuscular injection method was conducted for vaccination and booster of 0.1 ml vaccine into the body, with the dosage of 5 Âµg/fish. Booster time interval was two week. Data were taken for fiveteen weeks. The parameters to observe were titer antibody and water quality. Futhermore, they were analized by Analysis of Variance and Duncanâs Multiple Range Test (DMRT). The result showed that cell debris A. hydrophila vaccination by 1-3 times booster with 2nd week time interval could increase the adaptive immune response through the increase titer of antibody (P<0.05) on African catfish. Vaccination with two time booster (D3) was the mostÂ effective method of vaccination.